POTENSI AMPAS KELAPA (Cocos nucifera L.) SEBAGAI ALTERNATIF BAHAN PEMBUATAN KERTAS KOMPOSIT - Retno Prasetia; Purbawati Purbawati; Halikianoor Halikianoor (Journal of Sustainable Transformation, 2022)
Coconut dregs is a waste that has non-wood fiber thus it is potential as a material for making composite paper. The use of coconut dregs in this study aims to determine its potential as a raw material for making composite paper through tensile resistance and tear resistance.             The making of composite paper in this study was carried out by combining coconut pulp and used HVS paper pulp. The design used was a completely randomized design (CRD) with 3 replications consisting of 3 treatments and a control. The data obtained were analyzed using the Anova test and the DMRT test with a level of 5%..             The highest paper tensile resistance test results were obtained by P1 which was 0.26 kN / m smaller than 1.26 kN / m (P0 as a control), as well as the highest paper tear resistance test results obtained by P2 at 340 mN smaller than 666 , 4 mN (P0 as control). Based on the data obtained, the addition of coconut dregs or not in making composite paper shows a potential that does not have a significant effect. This research has the potential to be developed for better paper quality.